Formação inicial docente: análise do curso de licenciatura em Matemática na Universidade Federal da Paraíba-Campus I a partir do projeto pedagógico do curso - Nascimento, Daniel Tavares do (2022)
This research has as general objective to analyze the initial formation of Mathematics teachers, having as locus the Federal University of Paraíba (UFPB), Campus I, based on the Pedagogical Project of the Course (PPC). The methodological way passes through a qualitative approach, of a documentary feature with descriptive procedure methods. The theme is discussed by documents that deal with educational policies and initial teacher training, such as the Law of Guidelines and Bases for National Education, the CNE resolution, the National Curricular Guidelines for Mathematics courses and the National Higher Education Assessment System (BRAZIL, 1996, 2001, 2002, 2015, 2019). The theoretical reference discusses teacher training, where we refer from (GATTI, 2009; GATTI, 2010; GATTI, 2013; GATTI, 2016; GATTI, 2018; GATTI, 2021), Libâneo (2015), (NÓVOA, 2016; NÓVOA, 2019) and discuss the history and characteristics of teacher training, current situations and problems, the curriculum of the Degrees, in addition to disciplinary and pedagogical knowledge; the importance of theory in teacher training, in addition to the discussion about the DCNs and other documents that deal directly with the training of Mathematics teachers. Regarding data collection, we accessed the National Curriculum Guidelines for Mathematics courses (DCNs) and the Pedagogical Course Project (PPC) of the Mathematics Degree Course at Campus I of UFPB. Data analysis was carried out by comparing the two documents from different perspectives, such as: Objective, profile of trainees, skills and competences, curriculum contents and verifying if both were in agreement. Posteriorly, charts were created to present the similarities and differences between these elements, as well as tables that demonstrate quantitative related to the Degree. It was found that the tripod: profile - skills and abilities - curriculum content, presented by the DCNs is covered by the PPC of the course responsible for training Mathematics teachers at Campus I of UFPB, with the exception that it must address the training process of their students more content related to Mathematics in Basic Education, taking into account the lack of these disciplines in the flowchart and the general objective of the course indicated by the Project.